succession - Grigoryeva, Elena (project baikal, 2021)
Does new always mean the best? Throughout the last century people had been actively trying to invent and build a new world. A world without old or obsolete things. The end of the millennium gave rise to an illusion that all achievements, disasters and confrontations of the previous ten centuries were left behind. But the new century has already brought so drastic changes that the attitude toward the past is no longer the same. The larger the wave of the new becomes, the more precious looks the succession, or the continuity of the past in the present. Is it pure coincidence that the English words “succession” and “success” have the same root? The Ise Shrine in Japan is rebuilt every 20 years because two previous generations of craftsmen are still alive at the time of each reconstruction. The tradition does not change. The technology, the aesthetic principles, the manner of understanding and feeling of beauty are passed from hand to hand. We have frequently referred to the period of creative rise in the middle of the last century, to the phenomenon of the “sixtiers”. Like the modernism itself, Siberian brutalism opposed the classical cannons, but today its audacious large-scale solutions look like a direct continuation of the centuries-old development of architecture. Today’s rebirth of interest in brutalism is not accidental. We believe in its recovery, of course, on a new level of comprehension and in new forms. Indeed, if the main function of the state in the 21st century is to provide conditions for human self-realisation with the use of cultural and historical identity, it is time to speak about SUCCESSION.